ILRI medium-term plan 2000-2002. Improving the productivity of smallholder livestock systems and protecting the natural resources that support them - International Livestock Research Institute (International Livestock Research Institute, 1999)
As ILRI developed its programmes for the year 2000 and beyond, the principles and choices set out in the strategic plan and the medium-term plan for 1998-2000 were reviewed with respect to new Developments in science, alternative suppliers, ILRI's comparative advantage and financing strategy. ILRI's priorities for 2000-20002 continue to follow those described in the MTP 1998-2000, and as approved by ILRI's Board, TAC and the CGIAR. This Report summarises the 1998 results and 1999 Developments, highlights changes for 2000, presents and discusses major features of the 2001-2002 project portfolio, and changes in milestones. Other presented topics include collaboration highlights, project cost components, centre staffing highlights, centre financial health indicators and financing plan. The 20 ILRI projects are presented in detail as an annex. Financial tables are also included in the document.